Whole tumour kinetics analysis of 18F-fluoromisonidazole dynamic PET scans of non-small cell lung cancer patients, and correlations with perfusion CT blood flow - McGowan, D; Skwarski, M; Papiez, B; Macpherson, R; Gleeson, F; Schnabel, J; Higgins, G; Fenwick, J (Springer Open, 2018)
Background: To determine the relative abilities of compartment models to describe time-courses of 18F-fluoromisonidazole (FMISO) tumour uptake in patients with advanced stage non-small cell lung cancer (NSCLC) imaged using dynamic positron emission tomography (dPET), and study correlations between values of the blood flow-related parameter K1 obtained from fits of the models and an independent blood flow measure obtained from perfusion CT (pCT). Methods: NSCLC patients had a 45 minute dynamic FMISO PET/CT scan followed by two static PET/CT acquisitions at two and four hours post-injection. Perfusion CT scanning was then performed consisting of a 45 second cine CT. Reversible and irreversible two-, three- and four-tissue compartment models were fitted to 30 time-activity-curves (TACs) obtained for 15 whole tumour structures in 9 patients, each imaged twice. Descriptions of the TACs provided by the models were compared using the Akaike and Bayesian information criteria (AIC and BIC) and leave-one-out cross-validation. The precision with which fitted model parameters estimated ground-truth uptake kinetics was determined using statistical simulation techniques. Blood flow from pCT was correlated with K1 from PET kinetic models in addition to FMISO uptake levels. Results: An irreversible three-tissue compartment model provided the best description of whole tumour FMISO uptake time-courses according to AIC, BIC and cross-validation scores totaled across the TACs. The simulation study indicated that this model also provided more precise estimates of FMISO uptake kinetics than other two- and three-tissue models. The K1 values obtained from fits of the irreversible three-tissue model correlated strongly with independent blood flow measurements obtained from pCT (Pearson r coefficient = 0.81). The correlation from the irreversible three-tissue model (r=0.81) was stronger than that from than K1 values obtained from fits of a two-tissue compartment model (r=0.68), or FMISO uptake levels in static images taken at time-points from tracer injection through to four hours later (maximum at two minutes, r=0.70). Conclusions: Time-courses of whole tumour FMISO uptake by advanced stage NSCLC are described best by an irreversible three-tissue compartment model. The K1 values obtained from fits of the irreversible three-tissue model correlated strongly with independent blood flow measurements obtained from perfusion CT (r=0.81).